The effects of NAD+ precursor (nicotinic acid and nicotinamide) supplementation on weight loss and related hormones: a systematic review and meta-regression analysis of randomized controlled trials - Baichuan, You; Gomes Reis, Marcela; Tavakoli, Sogand; Khodadadi, Navideh; Sohouli, Mohammad Hassan; Sernizon Guimarães, Nathalia (Frontiers in Nutrition, 2023)
Background: Despite the fact that obesity and overweight are serious major health problems worldwide, fighting against them is also considered a challenging issue. Several interventional studies have evaluated the potential weight-reduction effect of nicotinamide adenine dinucleotide (NAD+) precursor. In order to obtain a better viewpoint from them, this study aimed to comprehensively investigate the effects of NAD+ precursor supplementation on weight loss, adiponectin, and leptin.Methods: Scopus, PubMed/Medline, Web of Science, Cochrane, and Embase databases were searched using standard keywords to identify all controlled trials investigating the weight loss and related hormones effects of NAD+ precursor. Pooled weighted mean difference and 95% confidence intervals were achieved by random-effects model analysis for the best estimation of outcomes.Results: Twenty two treatment arms with 5144 participants' were included in this systematic review and meta-regression analysis. The pooled findings showed that NAD+ precursor supplementation has an effect on lowering BMI (weighted mean difference (WMD): -0.19 kg/m2, 95% confidence interval (CI): -0.29 to -0.09, P< 0.001) and increasing adiponectin (WMD: 1.59 µg/ml, 95% CI: 0.49 to 2.68, P= 0.004) in humans compared with control groups. However, no significant effect was observed on body weight and leptin. There was a significant relationship between doses of intervention with changes in BMI. In addition, subgroup analysis showed that BMI reduction was greater when receiving nicotinic acid (NA) supplementation than nicotinamide (NE) supplementation Conclusions: NAD+ precursor had significant effects on weight management with the reduction of BMI and increasing adiponectin.